2017
DOI: 10.1097/md.0000000000008823
|View full text |Cite
|
Sign up to set email alerts
|

Severe pertussis infection

Abstract: We aimed to investigate the clinicopathological features of pertussis in children admitted to a tertiary-care university hospital in Brazil.This was a retrospective cohort study of all pediatric hospital admissions with pertussis from January 1, 2008 to December 31, 2014. We also reported the autopsy findings in children who died.Fifty-five patients admitted to the hospital over the study period had laboratorial confirmation of Bordetella pertussis infection, 17 (30.9%) needed pediatric intensive care unit (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
3
11
1
1
Order By: Relevance
“…Infant baboons that were euthanized because of severe pertussis infection exhibited a pathology similar to that observed in fatal human cases of B. pertussis (7)(8)(9)16). In both hosts, subjects experienced descending disease, with pulmonary hemorrhage, edema, and fibrin deposits obstructing the terminal airways.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Infant baboons that were euthanized because of severe pertussis infection exhibited a pathology similar to that observed in fatal human cases of B. pertussis (7)(8)(9)16). In both hosts, subjects experienced descending disease, with pulmonary hemorrhage, edema, and fibrin deposits obstructing the terminal airways.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, 6-to 9-month-old (juvenile) baboons experience severe disease that lasts approximately 2 weeks, followed by a 2-to 3-week convalescence, resulting in a return to full health (10). We examined the histopathology of 5-to 6-week-old baboons that required euthanasia due to the severity of their disease following infection with B. pertussis, with the findings being similar to those reported for fatal human infant cases (7)(8)(9). In juvenile baboons, we found that the disease is highly inflammatory and concentrated to the lungs with signs of disease that would typically be diagnosed as acute respiratory distress syndrome (ARDS) and bronchopneumonia.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Reports have described the identification of leukocyte thrombi in small pulmonary blood vessels and speculated that vascular occlusion caused by leukocytosis results in increased pulmonary arterial pressure and establishment of pulmonary hypertension [48,49]. However, this finding is not supported in other clinicopathological studies [16,50]. If leukocytosis does promote the onset of pulmonary hypertension, this may be one mechanism by which PT indirectly promotes this pathology.…”
Section: Role Of Pt In Severe Infant Pertussismentioning
confidence: 99%